PENGARUH MOTIVASI, KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA PERUSAHAAN PERKEBUNAN NUSANTARA IX SEMARANG - Risca Eka Wijaya, 14.05.51.0022; Murdiyanto, Agus (Students Journal of Economic and Management, 2018)
Abstract This study aims to analyze the influence of Motivation, Leadership and Work Environment on Employee Performance Plantation Archipelago IX Semarang City. The population in this study is the total number of employees amounted to 120 respondents. The data used are primary data, that is data obtained directly from the source. The technique used for primary data collection is done by means of questionnaires to the respondents. The test of determination (RÂ²) indicate that employee performance can be explained by Motivation, Leadership and Work Environment of 57,7%, while the remaining is influenced by other variables outside of research. The f test indicate that Motivation, Leadership and Work Environment jointly significant effect on employee performance. The t test indicate that Motivation has a positive and significant impact on employee performance, Leadership has a positive and significant impact on employee performance, work environment has a positive and significant impact on employee performance.Keywords: Motivation, Leadership, Workplace Environment and Employee Performance